Case reportAcrodermatitis enteropathica (Danbolt-Closs syndrome) - diagnostical problems. Case report - Kaszuba, Aleksandra; Poznańska-Kurowska, Katarzyna; Pastuszka, Marta; Uczniak, Sebastian (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2010)
Acrodermatitis enteropathica (ADE) is a rare, recessive, lethal genetic or acquired disorder of hypozincemia. It can be caused by impaired intestinal absorption of zinc or by poor consumption of the mineral. It is characterized by skin lesions on acral and periorificial areas and may be associated to alopecia, diarrhea and increased frequency of infections. The SLC39A family consists of 14 members which are thought to control zinc uptake into the cytoplasm. Among these, ZIP4 is known to be particularly important for zinc homeostasis. Mutations in this gene cause acrodermatitis enteropathica. Not only hereditary, but also acquired forms of ADE have been described. Acquired ADE can be secondary to deficient intake of zinc, malabsorption syndromes, alcoholism, jejuno-transverse colon anastomosis, pancreaticoduodenectomy, HIV infection, malignancies, chronic renal failure, pregnancy or drugs. Treatment of underlying disorder and zinc replacement therapy results in rapid resolution of the condition. ADE patients require lifelong zinc supplementation, with repeated serum zinc determinations. We report a case of a two-year-old girl, who because of wrong diagnosis was several times hospitalized and treated with systemic and topical antibiotics, antifungals, antivirals and antihistamines. Only short-termed improvement of skin and mucous lesions was received. She was also diagnosed in the direction of immunosupression. Only the proper diagnosis of acrodermatitis enteropathica and introduction of the treatment with oral zinc supplementation allowed to receive long-lasting and long-awaited improvement of skin and mucous lesions. The presented case report reveals the diagnostic problems with ADE, that must be taken into account while making differential diagnosis amongst a wide range of other dermatological disorders especially in young children. Only the rapid proper diagnosis allows to avoid such complications as severe dermatitis, chronic diarrhoea, retardation of growth and development, alopecia and increased proneness to infections.